Factors associated with discharge delay and direct discharge home from paediatric intensive care. (26th February 2020) - Kennedy, Tessa K; Numa, Andrew
Abstract : Aim: To examine the patient and hospital admission characteristics associated with direct discharge home from paediatric intensive care. Methods: This was a single‐centre retrospective analysis of all admissions to a tertiary metropolitan general paediatric intensive care unit (ICU) surviving to discharge over a 10‐year period between 1 January 2007 and 31 December 2016, divided into two epochs defined by changes in health service structure. Patient and admission characteristics were compared between groups discharged direct to home and discharged to ward across these two epochs. Results: There was a marked increase in the annual rate of direct discharge to home from ICU between the two epochs (3.7–9.5%, P < 0.0001). There was an inverse relationship between monthly ICU activity and rates of direct discharge to home. Patients discharged directly home were significantly more likely to experience delay to discharge (46.4 vs. 30.7%, P < 0.0001), for that delay to exceed 24 h and comprise a greater proportion of total ICU length of stay. Bronchiolitis accounted for an increasing proportion of admissions between epochs (7.0–15.1%) and was over‐represented among patients discharged direct to home (up to 18.2%). Conclusions: The high observed rate of direct discharge home is likely to have resulted from increased delays to discharge and changes to patient admission characteristics, attributable to organisational restructuring and possibly changing approaches to clinical management of bronchiolitis. It is imperative to now consider how we ensure that our systems support the proper use of intensive care resources.